Silicon oxycarbide-tin nanocomposite derived from a UV crosslinked single source preceramic precursor as high-performance anode materials for Li-ion batteries. (June 2022) - Knozowski, Dominik; Sasikumar, Pradeep Vallachira Warriam; Dubey, Romain; Aebli, Marcel; Kravchyk, Kostiantyn V.; Trykowski, Grzegorz; Kovalenko, Maksym V.; Graule, Thomas; Wilamowska-Zawłocka, Monika; Blugan, Gurdial
Highlights: SiOC/Sn composite is prepared by an innovative and facile UV light-assisted synthesis. The synthesis through a PDC route leads to the preparation of a single-source precursor. UV-irradiation process in the presence of tin octoate improves cross-linking mechanism. Tin nanoparticles are uniformly dispersed in the ceramic matrix. SiOC/Sn electrodes exhibit high capacity, outstanding rate capability and cyclability. Abstract: In this work, we report an innovative and facile UV light-assisted synthesis of a nanocomposite based on silicon oxycarbide (SiOC) and tin nanoparticles. SiOC ceramic matrix, containing a conductive free carbon phase, participates in lithium-ion storage, and buffers the volume changes of Li-alloying/de-alloying material. The reported synthesis procedure through a polymer-derived ceramic route involves the preparation of a single-source precursor by UV crosslinking of a preceramic polymer in the presence of a tin precursor. Pyrolysis of this starting precursor at 1000 °C leads to a homogenous distribution of tin nanoparticles (25–35 nm) within the SiOC ceramic matrix, which is crucial for electrochemical stability of the material. SiOC/Sn nanocomposite tested as an anode for Li-ion battery exhibits high reversible capacity values (603 mAh g −1 at the current density of 74.4 mA g −1 ), outstanding rate capability (524 mAh g −1 at 2232 mA g −1 ), and superior stability (494 mAh g −1 after 250 charge/discharge cycles). Graphical abstract: Image, graphical abstract